The impact of electronic applications in improving Syrian passport services in the Immigration and Passports Branch in Tartous (Latakia University Journal - Economic and Legal Sciences Series, 2024)
improving the quality of services provided for issuing Syrian passports. Electronic applications are considered one of the modern technological means to facilitate the provision of services. In general, the study found that electronic applications through electronic platforms for booking and issuing Syrian passports and electronic applications for paying passport fees play an important role in influencing the quality of services provided by the Immigration and Passports Branch in Tartous for issuing Syrian passports. We used the descriptive analysis approach, relying on questionnaires distributed to citizens who obtained Syrian passports using an electronic platform, and we used the SPSS statistical program to analyze this data, and applied regression analysis to study the relationship between the dependent and independent variables.The most important results of this study are:-The electronic platform for booking and issuing Syrian passports affects the quality of services provided by the Immigration and Passports Branch in Tartous.-The application of electronic payments to pay Syrian passport fees affects the quality of services provided by the Immigration and Passports Branch in Tartous. -The electronic platform and electronic payment application contribute to improving the quality of services provided by the Immigration and Passports Branch in Tartous when issuing Syrian passports.